ANALISIS KELAYAKAN USAHA PETERNAKAN AYAM PETELUR MANDIRI - Tharsisius Pabendon; Nuraviva Sahelani (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2022)
This study aims to determine the feasibility of an independent layer chicken farming business in terms of financial and non-financial. To achieve this goal, the method used in this research is descriptive. For the purposes of analysis, the data used for the financial security assessment was obtained directly from the owner of the Independent Laying Chicken Farm, while for the non-financial assessment it was obtained from the owner of the Independent Laying Chicken Farm, workers, customers, the surrounding community, and other livestock entrepreneurs for comparison. using observation and interview techniques. To analyze To analyze the feasibility of a business from a financial point of view, B/C ratio analysis is used, while non-financial assessment with indicators of production aspects, market and marketing aspects, and environmental aspects is used source triangulation analysis. The results of the analysis of this study indicate that the Independent Laying Chicken Farm is feasible to be developed from a financial and non-financial perspective.